Barriers to Visibility in Supply Chains: Challenges and Opportunities of Artificial Intelligence Driven by Industry 4.0 Technologies - Delgado, Fernanda [UNESP]; Garrido, Susana; Bezerra, Barbara Stolte [UNESP] (MDPI, 2025)
Advancements in e-commerce and Industry 4.0 technologies have significantly improved communication and connectivity in supply chains. These technologies, particularly artificial intelligence driven by Industry 4.0 technologies (AI-IT4.0), have reshaped how products, services, and financial transactions are managed, emphasizing the importance of information sharing among supply chain participants to enhance inventory management, sales, and demand forecasting. However, sharing comprehensive information across supply chain stakeholders presents persistent challenges due to various barriers. This study seeks to review the current understanding of visibility barriers in supply chains, identify key obstacles, and suggest directions for future research. Using the PRISMA methodology, the study analyzed 20 articles, identifying 12 critical barriers to visibility. Bibliometric analysis has revealed growing interest in the topic since 2021, although evidence of collaborative research remains limited. A keyword co-occurrence analysis highlighted strong connections between visibility, supply chain management, sustainability, and artificial intelligence driven by industry 4.0 technologies, such as machine learning, predictive analytics, and digital twins. Future research should empirically investigate visibility barriers and explore the interplay between AI-TI4.0, visibility, and sustainable performance through case studies and quantitative approaches.
Keywords: artificial intelligence; barriers; Industry 4.0 technologies; information sharing; supply chain management; supply chain visibility